Enucleation with or without adjuvant therapy versus marsupialization with or without secondary enucleation in the treatment of keratocystic odontogenic tumors: A systematic review and meta-analysis. Issue 9 (September 2016) - Al-Moraissi, Essam Ahmed; Pogrel, M. Anthony; Ellis, Edward
Abstract: The purpose of this study was to compare the recurrence rate (RR) of keratocystic odontogenic tumors (KOTs) in patients who underwent enucleation with or without adjuvant therapy, to patients who underwent decompression with or without residual cystectomy. An extensive search of major databases through PubMed, EMBASE, and Cochrane CENTRAL was conducted to identify all relevant articles published without date and language restrictions from inception to December 2015. Relevant articles were selected based on the specific inclusion criteria. A weighted RR and odds ratio (OR) using a Mantel-Haenszel (M-H) test and random effect model with 95% confidence interval (CI) were performed. Meta-regression analysis was conducted to further identify the influence of the duration of follow-up periods on the overall OR. A total of 997 KOTs enrolled in 14 studies were included in this analysis. There was a significant advantage for the enucleation ± adjuvant therapy group in preventing recurrence for patients with KOTs (M-H, OR, 0.514; 95% CI, 0.302–0.875; p = 0.014). The overall pooled weighted RR for enucleation ± adjuvant therapy and decompression ± secondary cystectomy were 18.2% and 27.1%, respectively. The meta-regression analysis showed that duration of follow-up time did not significantly influence the OR of KOT recurrence (Q = 0.506, p = 0.646). In conclusion, initial cystectomy ± adjuvant therapy was associated with fewer recurrences than decompression ± secondary cystectomy. Highlights: Initial cystectomy ± adjuvant therapy had fewer recurrences than decompression ± secondary cystectomy. Enucleation ± adjuvant therapy in the treatment of KOTs decreases the incidence of recurrences by 48.6% compared with using decompression ± secondary cystectomy. The overall pooled weighted RR for enucleation ± adjuvant therapy and decompression ± secondary cystectomy were 18.2% (random: 95% CI = [14.3%, 22.8%]) and 27.1% (random: 95% CI = [18%, 38.5%]) respectively.